METABOLIC PROFILE ASSESSMENT OF PHYTOCHEMICALS IN CEIBA PENTANDRA (L.) GAERTN, FROM ZARIA CITY, NIGERIA - Dalhatu, A. S.; Imman, S. T.; Namadina, M. M.; Zainab Muhammad Sani; Muhammad, Y. Y. (FUDMA JOURNAL OF SCIENCES, 2020)
Ceiba pentandra (Silk cotton) is a multipurpose tree in the province of Zaria city, Kaduna State, Nigeria, which is being exposed to uncontrolled exploitation by the natives. Samples of the plant were collected from standing trees located at Zaria city: Kofar Gayan, Rimin Doko, Kwarbai, Kofar Doka and Kofar Kibo. The study was aimed at assessing the secondary metabolites in C. pentandra plant extracts of leaves, stem barks and roots This was achieved through subjecting the extracts to phytochemical screening and gas chromatography/mass spectrometry fingerprinting (metabolic profiling) of phytochemical markers. The results of the screening revealed flavonoids, saponins, steroids, tannins, triterpenoids and reducing sugars to be present in moderate variation, across the extracts. The metabolic fingerprinting indicated high variation among the phytochemicals obtained from the plant extracts. Where, twenty-seven (27) secondary metabolites were predicted from the methanol leaf extracts, twenty-five (25) from the methanol stem bark extracts and twenty-seven (27) from the methanol root extracts, out of which only one of the metabolites (2-hydroxypropyl ether) was predicted in all the extracts. Therefore, for a clearer and broader identification of these phytochemical markers, Nuclear Magnetic Resonance spectrometry (NMR) should be employed to determine the detailed chemical structures of the identified metabolites, which will help in determining their functions and how they can be used to improve the biodiversity of these tree species.